52‐4: Long‐lived Thermally Stable Blue OLED Achieving BT.2020 Color Gamut. Issue 1 (May 2017) - Hashimoto, Naoaki; Takita, Yusuke; Yamaoka, Ryohei; Nomura, Shiho; Sasaki, Toshiki; Yamagata, Sachiko; Suzuki, Tsunenori; Seo, Satoshi
Abstract : We developed a deep‐blue fluorescent organic light‐emitting diode (OLED) that is long‐lived and thermally stable. This blue OLED accommodates the BT.2020 color gamut for the first time in the world, and enables a longer lifetime than a conventional one while maintaining comparable power consumption in a full‐color OLED panel.